Analisis Hukum dalam Pengelolaan dan Konservasi Ekosistem Laut: Review Sistematik tentang Legal Fishing dan Implikasinya bagi Kenakaragaman hayati Laut: Analisis Hukum dalam Pengelolaan dan Konservasi Ekosistem Laut: Review Sistematik tentang Legal Fishing dan Implikasinya bagi Kenakaragaman hayati Laut - Junaidin; Adnan (Jurnal Sains dan Pendidikan Biologi, 2024)
Marine ecosystems play a crucial role in maintaining planetary health and human well-being, supporting over 230,000 species and serving as key regulators of the global climate and primary sources of food. However, human activities such as overfishing and habitat destruction pose significant threats to marine biodiversity and ecosystem stability. To address these issues, various legal regulations have been implemented, including catch quotas and marine protected areas, as outlined in the United Nations Convention on the Law of the Sea (UNCLOS) and the International Convention on the Conservation of Atlantic Tunas (ICCAT). Despite these measures, challenges such as inconsistent compliance and economic conflicts often hinder effective implementation. This study aims to evaluate how legal fishing regulations contribute to the management and conservation of marine ecosystems and their impact on marine biodiversity. The methodology involves a systematic review of relevant literature, assessing the effectiveness of legal frameworks and identifying implementation challenges. Findings indicate that while legal regulations provide a robust framework for fisheries management, challenges in enforcement and economic conflicts frequently obstruct conservation efforts. The study highlights the need for improved implementation and enforcement of regulations and the development of more effective strategies to protect marine ecosystems and ensure the sustainability of marine resources in the future.